2019
DOI: 10.1111/1759-7714.13202
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine marker staining pattern categorization of small‐sized pulmonary large cell neuroendocrine carcinoma

Abstract: Background The aim of this study was to identify subgroups with good or bad prognosis in patients with pulmonary large cell neuroendocrine carcinoma (LCNEC) based on immunostaining patterns with neuroendocrine markers and compare them with small cell lung carcinoma (SCLC). Methods From January 2001 to December 2017, of all patients with resected LCNEC and SCLC, we selected patients whose pathological tumor sizes were ≤30 mm in diameter (defined as small‐sized tumors) and who underwent complete resection with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The favorable results of SCLC-P may be associated with a higher proportion of stage I or a lower frequency of background fibrosis. We previously reported that NEC with low NE or INSM1 negative have a better prognosis, 18,31 which may be related to the possibility that NEC-P is frequently included in these groups. Some reports found no significant difference in prognosis between SCLC-P and SCLC-non-P, 3,4 while others reported that SCLC-P has a favorable prognosis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The favorable results of SCLC-P may be associated with a higher proportion of stage I or a lower frequency of background fibrosis. We previously reported that NEC with low NE or INSM1 negative have a better prognosis, 18,31 which may be related to the possibility that NEC-P is frequently included in these groups. Some reports found no significant difference in prognosis between SCLC-P and SCLC-non-P, 3,4 while others reported that SCLC-P has a favorable prognosis 32 .…”
Section: Discussionmentioning
confidence: 99%